Analisis Kebijakan Insentif Pajak Kendaraan Bermotor Dalam Meningkatkan Pendapatan Asli Daerah di Provinsi Nusa Tenggara Barat - Evva Junita Rahman; Muaidy Yasin; Ali Akbar Hidayat (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the Motor Vehicle Tax incentive policy based on the Governor of West Nusa Tenggara Regulation Number 9 of 2025 and its contribution to increasing Regional Original Revenue. This study uses a quantitative descriptive approach by utilizing secondary data from the Regional Revenue Management Agency of West Nusa Tenggara Province in 2025. Analysis techniques include income trend analysis, PKB contribution analysis to PAD, and elasticity analysis to measure the level of response of PAD to changes in PKB income before and after the incentive policy is implemented. The results of the study show that the PKB incentive policy is able to increase taxpayer compliance and encourage a significant increase in PKB revenue, especially in the early period of policy implementation. Although PKB's contribution to PAD is still in the "less" category, the contribution trend shows a consistent increase. The elasticity value from elastic to highly elastic shows that PKB acceptance has a strong influence on PAD growth. These findings show that the PKB incentive policy is effective as a regional fiscal instrument in the short term, but requires a follow-up strategy to maintain the sustainability of regional financial independence.